Answers

The Brainliest Answer!
2015-03-08T16:46:03+05:30
3a-2b-ab-(a-b+ab)+3ab+b-a

3a-2b-ab-a+b-ab+3ab+b-a
take same terms like this
3a-a-a -2b+b+b -ab-ab+3ab
3a-a-a=a
-2b+b+b=0
-ab-ab+3ab= -2ab+3ab=ab
=a+0+ab
=a+ab
=a(1+b)
1 5 1
2015-03-08T18:44:41+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
=3a-2b-ab-a+b-ab+3ab+b-a
=(3a-a-a)+(-2b+b+b)+(-ab-ab+3ab)
=a+0+ab
=a+ab
=a(1+b)
0